Study on Numerical Simulation of Geometric Elements of Blasting Funnel Based on PFC5.0 - Wenle Gao; Zehua Zhang; Baojie Li; Kunpeng Li (Shock and Vibration)
Based on the particle flow code (PFC2D) within the discrete element method (DEM), the rock mass model was established according to the site rock conditions and the rock mass blasting was simulated by the explosive particle expansion method. The influence of various parameters (the peak pressure action coefficient of the borehole wall, explosive particle buried depth, and charge mode) in the explosive particle expansion method on blasting effect was investigated. Furthermore, the relationship between the various parameters and the geometry size of the blasting crater was obtained. By comparing the size of blasting crater in the field blasting test and numerical simulation example, the reliability of rock mass blasting simulated by the explosive particle expansion method using PFC is verified. The result shows that this paper provides a reliable new numerical simulation method for rock mass blasting and can be used to guide field blasting.